Historiographic review of the history of Aktobe (Journal of history, 2021)
At present, historiography occupies a special place in the development of Russian historical science. The historiographic definition of the history of the city of Aktobe, to a certain extent, contributes to an increase in the quality and effectiveness of historical research. According to the study of the history of the city of Aktobe, various historical chronicles are revealed since the founding of the Aktobe fortress. Historiographic analysis, sources and periodicals show what they tried to reflect in the study of the his tory of the city of Aktobe.One of the proofs of this study is the economic and literary newspaper «Aktobe Vestnik», the news paper «Aktyubinskaya Pravda», which are stored in the Aktobe State Archives. In addition, the newspaper«Stepnaya Pravda» and the chronicle requisites «Monuments of the Turgai Region» and other archival funds, which are rarely stored in the archival funds, make it possible to study the history of the city. The historical significance of the construction of the OrenburgTashkent railway, which became an important part of the city of Aktobe, was recorded in the expeditions of A.A. Kaufman during his visit to Turgai. This railway line, which is very relevant for Kazakhstan, is also the basis for writing the history of the city. The information obtained from the pages of periodicals is based on the history of Aktobe and the works of Russian historians. In particular, several historical works were written concerning the city of Aktobe. Thus, the collection of works by M. K. Tazhibaev and G. S. Sultangalieva tells how Aktobe acquired the status of a district town and became the center of the region. Since the Aktobe region is a multinational region, it is possible to trace in the works of the authors how many nationalities have migrated and urban planning is expanding from year to year. However, there are undisclosed sides tothe history of Aktobe.Key words: Aktobe city, district, fortress, mosque, school, OrenburgTashkent railway.